Why Is There Universal Macrobehavior? Renormalization Group Explanation as Noncausal Explanation. Issue 5 (December 2014) - Reutlinger, Alexander
Abstract : Renormalization group (RG) methods are an established strategy to explain how it is possible that microscopically different systems exhibit virtually the same macrobehavior when undergoing phase transitions. I argue—in agreement with Robert Batterman—that RG explanations are noncausal explanations. However, Batterman misidentifies the reason that RG explanations are noncausal: it is not the case that an explanation is noncausal if it ignores causal details. I propose an alternative argument, according to which RG explanations are noncausal explanations because their explanatory power is due to the application of mathematical operations, which do not serve the purpose of representing causal relations.